Agencing practices: a historical exploration of shopping bags. Issue 1 (2nd January 2016) - Hagberg, Johan
Abstract : The purpose of this paper is to explore the dynamic process of agencing through a practice-based historical analysis of shopping bags. This paper draws upon practice-based studies regarding consumption and markets and is based on an archive study of a Swedish packaging magazine from 1935 to 2013. The paper analyses the transformation of shopping bags from their introduction in shopping to the current situation of them being taken for granted, but at the same time, contested. The paper shows how shopping bags over time have been included in and contributed to the shaping of different practices and have been, in turn, transformed by these practices. The case of shopping bags suggests that agencing is a process in which capacity to act is acquired by continuous arranging of elements in different practices, as well as adjustments of these elements in relation to each other.